The impact of changes in second pension pillars on public finances in central and Eastern Europe - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the impact of recent changes in second pension pillars of three Central and Eastern European Countries. The paper seeks to answer the following questions: i) what is the impact on the sustainability of Poland's pension system of the decrease in the pension contribution going to the second pension pillar from 7.3% to 2.3% in 2011; ii) what are the implications of the recent changes on gross replacement rates; iii) does the weakening of the Polish second pension system have a different impact on pension system sustainability than a similar move in a Hungarian-style pension system with a defined-benefit first pillar and iv) how does Estonia's temporary decrease in pension contributions compensated by temporarily higher future rates affect pension sustainability in that country. The simulation results show that in our baseline scenario the Polish move would permanently lower future pension-system debt, chiefly as a result of a cut in replacement rates. But using a combination of pessimistic assumptions including strong population ageing, low real wage growth and a high indexation of existing pension benefits, coupled with bringing in tax expenditures related to the third voluntary pension pillar and an increase in the share of minimum pensions leads to higher pension system deficits and eventually more public debt at a very long horizon. The simulations also suggest that the Hungarian pension reversal reduces deficit and debt only temporarily, mainly because of Hungary's costly defined-benefit first pension pillar: the weakening of the second pillar is tantamount to swapping low current replacement rates (in the defined-contribution second pillar) against high future replacement rates in the defined-benefit first pension pillar. Finally, results show that the Estonian move will increase public debt only very moderately in the long run, even though this result is sensitive to the effective interest rate on public debt.
Keywords: H55; J32; 330; pension system; pension reversal; defined benefit; defined contribution; public finances; Central and Eastern Europe